10-13 ЁШЛИ ЯККАКУРАШЧИЛАР ҲАРАКАТ ТАЙЁРГАРЛИКЛАРИНИНГ ХУСУСИЯТЛАРИ ТЎҒРИСИДАГИ АХБОРОТЛАРНИ ОБЪЕКТИВЛАШТИРИШ (қиличбоз рапирачилар мисолида) - Тажибаев, С.С. (SCIENCE and SOCIETY, 2017)
In the present article the datas about the age features of development of moving qualities are given: speed, force, high-speed force, dexterity, flexibility and endurance of young fencers at the age of 10-13.
Keywords: young fencers; speed; force; high-speed force; dexterity; endurance; flexibility; means; methods